Effects of normothermic microwave irradiation on CD44+/CD24‒ in breast cancer MDA-MB-231 and MCF-7 cell lines. Issue 1 (2nd January 2020) - Asano, Mamiko; Tanaka, Satoshi; Sakaguchi, Minoru
ABSTRACT: We previously reported that MDA-MB-231 and MCF-7 cells, which are breast cancer cell lines and have cancer and cancer-initiating cells (CICs), were killed following normothermic microwave irradiation in which the cellular temperature was maintained at 37°C. In this study, we investigated the percentages of live or dead cells among CD44 + /CD24 − cells, which were defined as CICs among MDA-MB-231 and MCF-7 cells, and other types of cells in response to microwave irradiation. CD44 + /CD24 − cells among MDA-MB-231 cells were killed, thereby decreasing the number of cells, whereas the number of live CD44 + /CD24 − MCF-7 cells was increased following microwave irradiation. Moreover, adhesion, invasion, and migration were decreased in MDA-MB-231 cells, and the activation of matrix metalloproteinase-2 (MMP-2) in MDA-MB-231 cells was increased following microwave irradiation. These decreased cell activities might have been caused by MMP-2 activation and population changes in CD44 + /CD24 − in MDA-MB-231 cells. Abbreviations: APC: allophecocyanin; CBB: coomassie Brilliant Blue; CD: cluster of differentiation; CICs: cancer-initiating cells; FACS: fluorescence-activated cell sorting; FBS: fetal bovine serum; FITC: fluorescein isothiocyanate; FTDT: finite-difference time domain; HER2: human epidermal growth factor receptor type 2; PI: propidium iodide. Graphical abstract: : Functional changes of MDA-MB-231 cells by normothermic microwave irradiation.